2023
DOI: 10.31219/osf.io/7jp6u
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The public’s perspectives on lifestyle-related behavior change for dementia risk reduction: a qualitative study

Abstract: Background: There is accumulating evidence that addressing modifiable risk and protective factors has an impact on dementia rates. Insight into the public’s perspectives on dementia risk reduction is needed to inform future individual-level interventions and public health approaches.Objective: This study explores the publics’ openness towards dementia risk reduction and willingness towards changing lifestyle behavior to reduce the future risk for dementia.Methods: Using a screening questionnaire, participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…Formulating coping responses to overcome specific barriers and cope with difficult situations may further facilitate goal achievement [51]. In earlier qualitative research [11], we observed that low perceived control frequently resulted from earlier failed attempts to change lifestyle behavior. This underscores the importance of providing support to individuals who experience relapse, for example by encouraging them to view it as a part of the behavior change process and use it as an opportunity to learn from the experience [52].…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Formulating coping responses to overcome specific barriers and cope with difficult situations may further facilitate goal achievement [51]. In earlier qualitative research [11], we observed that low perceived control frequently resulted from earlier failed attempts to change lifestyle behavior. This underscores the importance of providing support to individuals who experience relapse, for example by encouraging them to view it as a part of the behavior change process and use it as an opportunity to learn from the experience [52].…”
Section: Discussionmentioning
confidence: 85%
“…In this cross-sectional study, we used a screening questionnaire to identify individuals with room to improve their lifestyle behavior and we invited them for a follow-up questionnaire to explore sociocognitive determinants of these behaviors. The study protocol was pre-registered [17] and materials and data to replicate the findings are open access available [18]. The findings are reported using the Strengthening the Reporting of Observational studies in Epidemiology (STROBE) checklist [19].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations